The Health Status of Electronics Women Workers in Relation to Their Lifestyle - Lim, Hwei Mian (2000)
This study aims to examine the lifestyle factors that affect the women workers' health status. Women from selected factories who were Malaysians, production workers aged 17 and above, and bad worked for at least one year in their current factory were invited to participate in the study on a voluntary basis. The final number of respondents was 484 women. The data was collected using a pre-coded questionnaire. Anthropometric measurements (weight and height) were obtained to calculate body mass index (BMI). Further study was conducted among a sub-sample of women (33) to obtain